Influence Of Problem Based Learning Model on Study Results of Science Students Class V Elementary School in SDIT Lentera Hati Ponorogo - Hanifah, Wafa Dani; Sukamti, Sukamti; Winahyu, Sri Estu (Angstrom Centre of Education, 2023)
This study is intended to identify the influence of the use of the Problem Based Learning model on the science learning outcomes of grade V elementary school students. The approach used is quantitative with quasy experimental design methods. The results showed that the PBL model positively affected student science learning outcomes. Proven based on the average science learning outcomes of experimental classes that were given treatment using the PBL model had a difference of 12.75 superior to control classes that did not use the PBL model in their learning activities. Through the results of the independent sample t-test hypothesis test, it was also found that the value of Sig. 0.001 < 0.05. It can be concluded that Ha is accepted so that there is a positive influence on the implementation of the Problem Based Learning model on the results of learning science for grade V students at SDIT Lentera Hati.